OPTIMIZATION OF PALLIATIVE CHEMOTHERAPY AND IMPROVEMENT OF QUALITY OF LIFE IN BREAST CANCER WITH LIVER METASTASES - Khalmatov Bahrom Akbarovich (Modern American Journals, 2025)
Breast cancer with liver metastases represents an advanced oncological condition characterized by poor prognosis, impaired hepatic function, aggressive tumor biology, and multidimensional quality-of-life decline. Palliative chemotherapy remains the core therapeutic strategy in this setting; however, its optimization requires a sophisticated, patient-centered, and biologically informed approach. This article provides a comprehensive analysis of modern strategies for optimizing palliative chemotherapy in patients with breast cancer and liver metastases, emphasizing individualized drug selection, liver-function–adapted dosing algorithms, integration of targeted and immunotherapeutic agents, and holistic supportive care. Key systemic therapy classes—including taxanes, anthracyclines, capecitabine, eribulin, HER2-targeted agents, CDK4/6 inhibitors, and immune checkpoint inhibitors—are evaluated in relation to hepatic metabolism, clinical outcomes, and tolerability. The article further explores strategies that address symptom burden, psychosocial stress, nutritional decline, and functional capacity, which collectively define quality of life in metastatic disease. Two comprehensive tables summarize therapeutic agents and quality-of-life interventions, while a conceptual diagram illustrates the integrated model of optimized palliative care. The findings highlight that a personalized, multidisciplinary, and toxicity-conscious approach significantly improves survival expectations and patient well-being in liver-metastatic breast cancer.
Keywords: Breast cancer; liver metastases; palliative chemotherapy; hepatic impairment; targeted therapy; immunotherapy; quality of life; supportive care; metastatic disease management; oncology.